Features of the Formation of Interpersonal Communication of Scientific and Pedagogical Employees of Universities - Khnykina, Oksana (Międzynarodowej Akademii Nauk Stosowanych w Łomży, 2025)
The article describes that the accelerated pace of people's lives leads to the replacement of deep spiritual-emotional relationships with functional-role ones, characterized by superficiality, and become a certain psychological protection against the sensory-emotional overload of the individual. Peculiarities of interpersonal communication of scientific and pedagogical workers were singled out: empathy, sympathy, reflection, mutual understanding, decentralization, identification, constructive ways of interaction, need for communication, and level of loneliness. It is described that interpersonal communication is the process of forming an individual's emotional relationships with subjects who surround him, which involves an emotional attitude toward each other, mutual social cognition, and a certain way of behavior toward each other. It was revealed that the respondents have a dominant manipulative orientation in communication.
Keywords: Communication, Scientific and Pedagogical Workers; Joint Activities; Interpersonal Relations